Vascularized composite allograft‐specific characteristics of immune responses. (21st March 2016) - Issa, Fadi
Summary: Vascularized composite allograft (VCA) transplantation, or reconstructive transplantation, has revolutionized the treatment of complex tissue and functional defects. Despite arriving during an age in which the immunology of solid organ transplant rejection has been investigated in much detail, these transplants have offered new perspectives from which to explore the immunobiology of transplantation. VCAs have a number of unique molecular, cellular, and architectural features which alter the character and intensity of the rejection response. While much is yet to be clarified, an understanding of these distinct mechanisms affords new possibilities for the control of immune responses in an effort to improve outcomes after VCA transplantation.